Strategic financial controlling instruments co of the commercial bank (Economics and region, 2018)
We consider the role of controlling in strategic management of the organization system. We ёanalysed the Balanced Scorecard and controlling tools in the system of financial management of commercial banks. A model of building a Balanced Scorecard of commercial bank in the market of non-traditional banking services was suggested.
Keywords: strategic financial controlling; Balanced Scorecard; a commercial bank; financial management; banking services